A comparative scanning electron microscopy study between the effect of an ultrasonic scaler, reciprocating handpiece, and combined approach on the root surface topography in subgingival debridement. Issue 4 (22nd June 2020) - Dassatti, Leonardo; Manicone, Paolo Francesco; Lauricella, Selenia; Pastorino, Roberta; Filetici, Pierfrancesco; Nicoletti, Fabrizio; D'Addona, Antonio
Abstract: Objective: This study aimed to analyze the effectiveness of root‐shape inserts mounted on a reciprocating handpiece during the procedure of root surface debridement (RSD) on extracted teeth. Three different approaches were compared: ultrasonic scaling, employment of root‐shape inserts mounted on a reciprocating handpiece, and a combination of both. Materials and Methods: A total of 51 extracted teeth were divided into three groups. The first group was instrumented with an ultrasonic scaler, the second group with flexible root‐shape inserts mounted on a reciprocating handpiece (grain size 40, 15, and 4 μm), whereas the final group underwent a combination of both approaches. The time required for the instrumentation was taken. The specimens were subjected to optical and scanning electron microscopy (SEM), and the photographs were evaluated by three examiners who were blinded to the study. The parameters included were: SEM roughness index (SRI) for the roughness calculation, remaining calculus Index (RCI) to evaluate the residual calculus deposits, and loss of tooth substance index (LTSI) to evaluate the loss of tooth substance caused by instrumentation. Result: The results revealed that the time taken for the instrumentation was on average longer when the root‐shape inserts were employed alone, meanwhile the combined approach did not show significant difference in comparison with the ultrasonic scaling. The lower average RCI was obtained with a combined approach. The use of root‐shape inserts seems to cause a moderate increase in LTSI, especially in a combined approach, whereas it resulted in a better average SRI. Conclusion: The employment of root‐shape inserts seems to be effective in the RSD for its ability to obtain a smooth and calculus‐free instrumented surface, especially when used in combination with an ultrasonic scaler, and their use can so represent a valid approach to be tested in further in vivo studies.